Microsecond MD Simulation and Multiple-Conformation Virtual Screening to Identify Potential Anti-COVID-19 Inhibitors Against SARS-CoV-2 Main Protease - Selvaraj, Chandrabose; Panwar, Umesh; Dinesh, Dhurvas Chandrasekaran; Boura, Evzen; Singh, Poonam; Dubey, Vikash Kumar; Singh, Sanjeev Kumar (Frontiers in Chemistry, 2021)
The recent pandemic outbreak of COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), raised global health and economic concerns. Phylogenetically, SARS-CoV-2 is closely related to SARS-CoV, and both encode the enzyme main protease (Mpro/3CLpro), which can be a potential target inhibiting viral replication. Through this work, we have compiled the structural aspects of Mpro conformational changes, with molecular modeling and 1 μs MD simulations. Long scale MD simulation resolves the mechanism role of crucial amino acids involved in protein stability, followed by ensemble docking provides potential compounds from the Traditional Chinese Medicine (TCM) database. These lead compounds directly interact with active site residues (His41, Gly143, and Cys145) of Mpro, which plays a crucial role in the enzymatic activity. Through the binding mode analysis in the S1, S1′, S2 and S4 binding subsites, screened compounds may be functional for the distortion of the oxyanion hole in the reaction mechanism, and it may lead to the inhibition of Mpro in SARS-CoV-2. The hit compounds are naturally occurring compounds, they provide a sustainable and readily available option for medical treatment in humans infected by SARS-CoV-2. Henceforth, extensive analysis through molecular modeling approaches explained that the proposed molecules might be promising SARS-CoV-2 inhibitors for the inhibition of COVID-19, subjected to experimental validation.